CORPORATE ZAKAT IMPLEMENTATION: CHALLENGES AND OPPORTUNITIES IN MODERN ECONOMY - Walidah, Ziyana (CV. Lafadz Jaya, 2024)
Corporate zakat is an emerging concept in the modern economic system, where Islamic financial principles are applied to ensure wealth redistribution and social justice. While zakat is traditionally known as a personal obligation, corporate zakat extends this duty to business entities, particularly in Muslim-majority countries. This article explores the implementation of corporate zakat, focusing on the challenges and opportunities it presents in the modern economic context. Corporate zakat has the potential to significantly impact social welfare by channeling funds to the less fortunate, while simultaneously enhancing corporate social responsibility (CSR) frameworks. However, its implementation faces several challenges, including low corporate awareness, lack of clear regulations, and inconsistent calculation methods. This paper reviews existing literature on corporate zakat, providing a comprehensive analysis of its role in fostering economic justice and social equality. Furthermore, the article examines potential strategies for overcoming challenges, including governmental regulation, corporate governance models, and collaboration with zakat institutions. The opportunities for corporate zakat, particularly in addressing poverty and inequality, demonstrate its relevance in today’s economic landscape, especially as businesses aim for more sustainable and ethical practices.